Is atopic dermatitis always atopic dermatitis? - Stańczyk-Przyłuska, Anna (Przewodnik Lekarza/Guide for GPs, 2011)
Atopic dermatitis is common in children. It is diagnosed in 4.7-6.5% Polish children. Diagnostic criteria have been set up by Hanifin and Rajka 30 years ago and are still valid. However, atopic dermatitis is diagnosed too frequent. Such situation occurs in the course of many other skin diseases: seborrheic or contact dermatitis. Miliaria, dermatomycosis, bacterial and viral infections, parasitic infestations can make the diagnosis difficult. Easy formation of skin changes in children and also occurrence of such changes in many disease entities can significantly complicate diagnose setting.